Accuracy of Doppler blood pressure measurement in HeartMate 3 ventricular assist device patients. (1st October 2020) - Li, Song; Beckman, Jennifer A.; Welch, Nathan G.; Cheng, Richard K.; Rockom, Sunny W.; Levy, Wayne C.; O'Brien, Kevin D.; Dardas, Todd F.; Lin, Shin; Leary, Peter J.; Kirkpatrick, James; McCabe, James M.; et al.
Abstract: Aims: Optimal blood pressure (BP) control is imperative to reduce complications, especially strokes, in continuous flow ventricular assist device (VAD) patients. Doppler BP has been shown to be an accurate and reliable non‐invasive BP measurement method in HeartMate II and HVAD patients. We examined whether Doppler BP is also accurate in patients with the HeartMate 3 VAD. Methods and results: In a prospective, longitudinal cohort of HeartMate 3 patients, arterial line BP and simultaneously measured Doppler opening pressure were obtained. Correlation and agreement between Doppler opening pressure and arterial line mean arterial pressure (MAP) versus systolic blood pressure (SBP) were analysed, as well as the effect of pulse pressure on the accuracy of Doppler opening pressure. A total of 589 pairs of simultaneous Doppler opening pressure and arterial line pressure readings were obtained in 43 patients. Doppler opening pressure had good correlation with intra‐arterial MAP ( r  = 0.754) and more closely approximated MAP than SBP (mean error 2.0 vs. −8.6 mmHg). Pulse pressure did not have a clinically significant impact on the accuracy of the Doppler BP method. These results in HeartMate 3 patients are very similar to previous results in HeartMate II and HVAD patients. Conclusions: Doppler BP method should be the default non‐invasive BP measurement method in continuous flow VAD patients including patients implanted with the HeartMate 3.